Magnetic resonance imaging in breast cancer management in the context of neo-adjuvant chemotherapy. (December 2018) - Taourel, P.; Pages, E.; Millet, I.; Bourgier, C.; Rouanet, P.; Jacot, W.; Crochet, P.; Azria, D.
Abstract: This review discusses the clinical applications of magnetic resonance imaging (MRI) for the assessment of neo-adjuvant chemotherapy (NAC) indication, axillary lymph node status, preNAC cancer prognosis, early and intermediate response to NAC, and post-NAC residual disease in patients with breast cancer. Contrast-enhanced MRI with analysis of the tumor morphological features and qualitative enhancement kinetics must be considered as the standard method for pre-NAC breast cancer staging and post-NAC residual disease assessment. Diffusion-weighted imaging (DWI) is easy to perform and may increase the specificity of breast MRI for tumor staging, and also for the assessment of tumor multifocality and multicentricity and lymph node status. It also provides an ancillary added value in the early and post-NAC response evaluation. Changes in the functional tumor volume are the main criterion for the early response analysis. Other MRI methods, such as quantitative perfusion analysis, MR spectroscopy and texture analysis, are still under study.